Analysis on The Society Indicator of Corporate Social Responsibility (CSR) of PT Antam - Sari, Nuraini; Wijaya, Michael (Binus Business Review, 2013)
Stakeholders believe that CSR report of a company provides significant information as well as the financial information reported in financial statement. The purpose of this research is to analyze the comprehensiveness and information on society indicator stated in the Corporate Social Responsibility (CSR) reporting. The Global Reporting Initiativeâs (GRI) Sustainability Reporting Guidelines (version 3.1) provides indicators to analyze the CSR of company. This research focuses on society aspect as one of the performance indicators. Comprehensive reporting contains three types of information: (i) vision and goals, (ii) management approach, and (iii) performance indicator. The methodology used in this research was data collection. This research analyzed the disclosure of society aspect by PT Antam on their financial statement and annual CSR report for the year 2012. The result of this research explains that PT Antamâs sustainability report for the year 2012 was comprehensive because they reported all the six aspects of society indicator. However, PT Antam failed to report the total value of financial and in kind contributions to political parties, politicians, and related institutions by country (SO6) as part of public policy aspect in their sustainability report.